The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acscatal.9b03113
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Valence State of Ru Species on CeO2 Supports: Support Shape Effect and Its Influence on CO Oxidation

Abstract: In this work, ruthenium (Ru) catalysts supported on CeO2 nanorods (NR), nanocubes (NC), and nanoctahedra (NO) were comparatively investigated to correlate the shape and exposed surface planes ({100}, {110}, and {111}) of nanoscale CeO2 supports with their low-temperature CO oxidation activity. Within the 5Ru/CeO2-r catalysts with three morphologies after reduction treatment, the Ru supported on CeO2 NR exhibited enhanced low-temperature (<100 °C) hydrogen consumption and superior room-temperature CO oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 90 publications
(161 reference statements)
5
129
0
Order By: Relevance
“…The intrinsic gaseous CO 2 exhibited two peaks at 2335 and 2360 cm −1 , respectively, and gaseous CO preserved its characteristic peak around 2177 cm −1 . [ 18 ] We found that when CO was introduced into the reaction cell, a new peak located at 2110 cm −1 instantly appeared even at the start temperature of 50 °C, clear evidence of linearly adsorbed CO on Pt. [ 5,42 ] This suggested that L‐Pt@CeO 2 catalyst manifested the high affinity toward CO.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…The intrinsic gaseous CO 2 exhibited two peaks at 2335 and 2360 cm −1 , respectively, and gaseous CO preserved its characteristic peak around 2177 cm −1 . [ 18 ] We found that when CO was introduced into the reaction cell, a new peak located at 2110 cm −1 instantly appeared even at the start temperature of 50 °C, clear evidence of linearly adsorbed CO on Pt. [ 5,42 ] This suggested that L‐Pt@CeO 2 catalyst manifested the high affinity toward CO.…”
Section: Figurementioning
confidence: 99%
“…[ 13–17 ] Surface defect engineering of the metal oxide supporting particles has been developed and refined to enhance support coupling with noble MNPs. [ 18–20 ] However, sophisticated pretreatment of the metal oxide supports and complicated synthetic procedures of noble MNPs still hinder their wide applications. It is challenging to establish a straightforward method to synthesize uniform catalysts in which preformed PGM nanoparticles are homogeneously mixed with metal oxide supports via strong surface coupling to retard the aggregation issue.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In literature, the observed O 1s peaks around 530 eV in CeO 2-x are typically ascribed to three oxygen species: lattice oxygen; oxygen vacancy; and surface-chem- isorbed oxygen species or oxygen in hydroxyl groups. [38,39] Due to the high concentration of surface oxygen vacancy, [24] the peaks at 529.3 and 531.4 eV are assigned to lattice oxygen (O L ) and oxygen vacancy/defects (O V ) on the surface of CeO 2 NR, respectively. The relative concentration of O v is calculated by the integrated peak area ratio of O species…”
Section: Chemical and Catalytic Propertiesmentioning
confidence: 99%